Improving grammar teaching pedagogy via pos tagging online / Ruzana Omar - Omar, Ruzana (2020)
Grammar is one of the components of learning English, and its fundamental feature is Parts of Speech, where the majority of Malaysian students of higher institutions are still having difficulties to understand its use in sentences. The aim of this study is to compare conventional methods of grammar instruction with e-learning methods on their effectiveness of teaching Parts of speech. The Stanford PoS Tagging method was used in the phrases extracted from The New Straits Times Online (NST Online) posts to determine the part-of-speech of each word. This quantitative forensic analysis adopted a comparative approach in assessing its findings. These results of the study showed a discrepancy of significance between student score using E-paper and student score not using E-paper in Grammar learning Independent t-testing to compare mean between the two groups was carried out. The results indicate a significance difference between the two students score classes (p-value= 0.007, t= -2.774). The students' mean output of E-paper indicates a higher percentage compared to those who do not use E-paper. Since students spend most of their time on electronic devices nowadays, this is an innovative way to draw their interest in spending their time reading content via electronic newspapers, while learning Grammar at the same time studying.